Community Service as a Contextual Learning Platform for Students: A Theoretical Study on Service Learning - Abdul Qodir; Siminto; Abu Muna Almaududi Ausat (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
This study aims to theoretically analyze the role of community service as a contextual learning platform for students through a service learning approach. Using a literature review method with a qualitative and descriptive analysis approach, this research focuses on enriching references regarding community service as an integral part of higher education processes. Data were obtained from scholarly articles on Google Scholar and various credible websites during the period 1984–2025. Out of a total of 50 articles found, after a rigorous selection process based on relevance and academic quality, 26 articles were used as the main sources of analysis. The findings indicate that service learning–based community service has a strong theoretical foundation in Experiential Learning Theory, Constructivist Learning Theory, Social Capital Theory, and Character Education Theory. Community service has been proven capable of integrating practical experience with academic reflection, developing students’ social, moral, and professional competencies, and providing positive socio-economic impacts for the community. These findings confirm that community service is a strategic instrument for shaping students as empowered, reflective, and ethical agents of social change.